Incorporating Student Experience and Transformative Learning into Curriculum Design and Planning of Undergraduate Theological Degrees : Final Report. - Ball, Les (Office for Learning and Teaching, 2013)
Final report from a project that examined the undergraduate theological education curriculum as it seeks to provide an increasingly diverse population of theological students with a transformative education. The project 1. Analysed the extent to which the needs and aspirations of students are being met through the current undergraduate theological curriculum. To this end, surveys of students were conducted at progressive stages of their studies. 2. Conducted research on claims by theological colleges of providing transformative learning experiences, and examined how these claims accord with student experience and with modern theories of transformative learning. If disparity was evident between the claims, the theories, and students' experience, individual colleges and the sector as a whole would need to develop a strategic approach to curriculum design and to the incorporation of transformative learning in a theological context. 3. Made recommendations for designing such a strategic approach. 4. Disseminated the results and recommendations of the study within the sector, and to other sectors.